2024
DOI: 10.1088/1674-1137/ad2a60
|View full text |Cite
|
Sign up to set email alerts
|

Study of bending angle and shadow in a new Schwarzschild-like black hole affected by plasma and non-plasma mediums*

Riasat Ali,
Tiecheng Xia,
Muhammad Awais
et al.

Abstract: In this study, we analyze the models of the deflection angle of a new Schwarzschild-like black hole and employ the optical metric of the black hole. To do so, we use the Gaussian curvature of the optical metric and the Gauss-Bonnet theorem, known as the Gibbons-Werner technique, to determine the deflection angle. Furthermore, we examine the deflection angle in the presence of the plasma medium and how the plasma medium affects the deflection angle. The deflection angle of the BH solution in the gauged super-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The contribution of the magnetic charge to the BH's greybody component will then be of greater interest, and it has also been concluded that the magnetic charge parameter in the Einstein GB gravity BH affects the field limitations of the weak DA. The weak DA is then determined using the expression shown in [36,39]…”
mentioning
confidence: 99%
“…The contribution of the magnetic charge to the BH's greybody component will then be of greater interest, and it has also been concluded that the magnetic charge parameter in the Einstein GB gravity BH affects the field limitations of the weak DA. The weak DA is then determined using the expression shown in [36,39]…”
mentioning
confidence: 99%